Probation and Social Work on Trial : Violent Offenders and Child Abusers / by Wendy Fitzgibbon. - Fitzgibbon, Wendy (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2011., 2017)
XI, 200 p. online resource.